2004
DOI: 10.1021/es049937g
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Diffusion in Layered Argillaceous Rocks:  A Case Study with Opalinus Clay

Abstract: Anisotropic diffusion was studied in Opalinus Clay, a potential host rock for disposal of spent fuel, vitrified high-level waste, and long-lived intermediate-level waste in Switzerland. Diffusion parallel to the bedding was measured using a radial through-diffusion technique and diffusion perpendicular to the bedding bythe classical (planar) through-diffusion technique. The samples used were from Mont Terri (MT) and from Benken (BE). Diffusion of HTO, 36Cl-, and 22Na+ parallel and perpendicular to the bedding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
106
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 24 publications
16
106
0
Order By: Relevance
“…The diffusion anisotropy estimated from HTO and 36 Cl -were consistent with those evaluated by Van Loon et al (2004a) from through-diffusion experiments. García-Gutiérrez et al (2008) applied the same experimental configuration to the Callovo-Oxfordian clay, and Samper et al (2008a) examined the reliability of estimating parameters in these experiments.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…The diffusion anisotropy estimated from HTO and 36 Cl -were consistent with those evaluated by Van Loon et al (2004a) from through-diffusion experiments. García-Gutiérrez et al (2008) applied the same experimental configuration to the Callovo-Oxfordian clay, and Samper et al (2008a) examined the reliability of estimating parameters in these experiments.…”
Section: Introductionsupporting
confidence: 72%
“…Extensive studies on the Opalinus clay (Switzerland) and Callovo-Oxfordian clay (France) have shown that the diffusion in these media is prominent in the direction parallel to the bedding plane (e.g., Van Loon et al, 2004a, 2004bGarcía-Gutiérrez et al, 2006Samper et al, 2008a). Numerical models of in-situ experiments performed in these areas have treated directional diffusivities as a diffusion tensor of rank two (e.g., Wersin et al, 2004;Yllera et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of diffusion of both water (measured using HTO) and chloride have also been made on several samples from Mont Terri. The ratio of the diffusion porosity for chloride to that of HTO is also between 0.5 and 0.7 (Pearson et al, 2003, Table A10.8;Van Loon et al, 2003, 2004. As a consequence, the value obtained from the overcore samples is the highest reliable value measured on…”
Section: Gradients In Pore Water Compositionmentioning
confidence: 99%
“…Previous studies collected and reported datasets of diffusive parameters from argillaceous formations (e.g., Aertsens et al 2004;van Loon et al 2004a and2004b;Descostes et al 2008;Appelo et al 2007). A summary of the diffusion parameters collected in clay-rock formations available in the literature was presented by Zheng et al (2011b For the reference case described in this report, the water diffusion coefficient of generic radionuclide is assumed to be equal to 1.08×10 -9 m 2 /s (Bianchi et al 2013;, and with radionuclide-specific effects (e.g., due to size and charge) not considered at this stage.…”
Section: Diffusion Coefficients In the Argillaceous Host Rockmentioning
confidence: 99%